Quality of Schooling and Quality of Schools for Indigenous Students in Guatemala, Mexico and Peru - Hernandez-Zavala, Martha; Patrinos, Harry Anthony; Sakellariou, Chris; Shapiro, Joseph (World Bank, Washington, DC, 2012)
A substantial gap in test scores exists between indigenous and non-indigenous students in Latin America. Using test score data for 3rd and 4th year primary school pupils in Guatemala and Peru, and 5th grade pupils in Mexico, the authors assess the magnitude of the indigenous and non-indigenous test score gap and identify the main family and school inputs contributing to the gap. A decomposition of the gap into its constituent components suggests that the proportion that is explained by family and school characteristics is between 41 and 75 percent of the overall test-score gap. Furthermore, family variables contribute more than school variables to the overall explained component.